2014
DOI: 10.1371/journal.pone.0092590
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Value of Research Data: A Citation Analysis of Oceanographic Data Sets

Abstract: Evaluation of scientific research is becoming increasingly reliant on publication-based bibliometric indicators, which may result in the devaluation of other scientific activities - such as data curation – that do not necessarily result in the production of scientific publications. This issue may undermine the movement to openly share and cite data sets in scientific publications because researchers are unlikely to devote the effort necessary to curate their research data if they are unlikely to receive credit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 70 publications
4
78
0
Order By: Relevance
“…To decrease concerns about scooping or free-riding, as a community we may want to develop guidelines for when collaboration would be appropriate or for when independent, dual publication on the same finding would benefit science. Additionally, researchers may benefit from sharing study data and materials by receiving increased citations (Belter, 2014;Piwowar & Vision, 2013). Scientists should create stronger norms for citing shared data and materials and-crucially-highly value such citations (Belter, 2014;Chen, Downs, & Shumacher, 2013;Nosek et al, 2015).…”
mentioning
confidence: 99%
“…To decrease concerns about scooping or free-riding, as a community we may want to develop guidelines for when collaboration would be appropriate or for when independent, dual publication on the same finding would benefit science. Additionally, researchers may benefit from sharing study data and materials by receiving increased citations (Belter, 2014;Piwowar & Vision, 2013). Scientists should create stronger norms for citing shared data and materials and-crucially-highly value such citations (Belter, 2014;Chen, Downs, & Shumacher, 2013;Nosek et al, 2015).…”
mentioning
confidence: 99%
“…These tools, tested in some LTER-Italy mountain sites (NextData project) and adopted as a data node in the H2020 project "eLTER", have been released as Open Source software, and can be used for a wider documentation, publication and sharing of data, which is one of the scopes of EcoNAOS. They have already been tested using small portions of ocenographic data coming from the Gulf of Venice (Bastianini et al 2015) and reported to be performing in presentation, update, querying and extraction of data. In our conception, the data life cycle is fully integrated into the research life cycle and the release of the dataset is previewed at different research stages (for different dataset versions).…”
Section: Methodsmentioning
confidence: 99%
“…This citation advantage, however, takes many years to show effect (Sears 2011) and is less than expected (Piwowar and Vision 2013). Inconsistent citation practices for data may contribute to underestimating the impact of data publications (Belter 2014).…”
Section: Open Access To Datamentioning
confidence: 98%